Insights into enhancing Centella asiatica organ cell biofactories via hairy root protein profiling - Alcalde, Miguel Angel; Hidalgo-Martinez, Diego; Bru Martínez, Roque; Sellés-Marchart, Susana; Bonfill, Mercedes; Palazon, Javier (Frontiers in Plant Science, 2023)
Recent advancements in plant biotechnology have led to the emergence of hairy roots as a promising biotechnological platform due to their potential for specialized metabolite production and rapid growth. In this study, proteomics analysis was used to obtain new insights into hairy root development, identify biomarkers, and potentially optimize genetic transformation for enhanced bioactive compound production in C.asiatica. This study involved the categorization of established C. asiatica hairy root lines based on their centelloside production capacity. These lines were classified as HIGH, MID, or LOW. Through meticulous label-free proteomic analysis, a total of 213 quantifiable proteins were successfully identified. The subsequent application of multivariate analysis elucidated distinct proteome differences and commonalities, particularly between the LOW line and other root lines. A protein network analysis revealed proteins related to essential processes such as photosynthesis and specialized metabolism. Potential biomarkers of different traits, were identified, including Tr-type G domain-containing protein and alcohol dehydrogenase in the HIGH group. Additionally, the control wild adventitious roots showcased a collection of proteins linked to photosynthesis. An intriguing finding arose from the presence of ornithine cyclodeaminase in the hairy roots. This protein serves as a traceable biomarker correlated with centelloside production capacity lines and serves as an indicator of the successful influence of Rhizobium-mediated genetic transformation. Based on the above, quantification of rol gene copy numbers through qPCR was undertaken, followed by gene expression measurements. However, the results of this quantitative analysis contradicted a uniform correlation with rol gene expression levels. Particularly noteworthy was the significantly higher expression observed in the HIGH line, specifically in relation to the rolD gene. The direct association and correlation of this gene with the ornithine cyclodeaminase biomarker further solidified this connection.